(untitled) - Malik, Waleed Haider (Washington, D.C., 2007)
Over the past 15 years, Singapore's judicial system has undergone a series of reforms aimed at modernization. In this report, Malik (affiliation not cited) examines the reform process from a management perspective. In addition to describing the strategies adopted to improve the system, Malik illuminates the political and economic context and analyzes the perceptions of various stakeholder groups. The focus is primarily on improvements in civil and commercial justice in the lower courts
Keywords: Law reform,Justice, Administration of; Singapore,Singapore